FEATURES OF THE USE OF ROASTING AND BAKERY EQUIPMENT IN THE HOTEL AND RESTAURANT BUSINESS - ANTONENKO, Artem; TOLOK, Galina; SUKHOMLYN, Dmytro; TERNOVSKIY, Daniil; TYSHKOVSKA, Anna; MYKHAYLICHENKO, Iryna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article describes the features of the interaction of thermal energy with food raw materials and food products and conducts an analytical review of the use of heat treatment for various technological processes in the food industry and hotel and restaurant business. The paper examines the peculiarities of the interaction of thermal energy with food raw materials and food products and provides an overview of the use of heat treatment for various technological processes in the food industry and hotel and restaurant business. Despite the number of scientific publications dedicated to the topic of technological equipment, in particular thermal heating, in Ukraine this is an insufficiently illuminated topic that requires research, taking into account the current conditions in the national economy. To create more rational technological processes, a combination of thermal heating with other energy carriers is used: steam, hot air, infrared heating, heated fat, vacuum, ultrasound. Heat treatment of food products in the cooking mode is divided into two stages: heating to a set temperature and maintaining this temperature until complete culinary readiness. The stepwise thermal heating method is also used, which ensures a high heating rate and avoids uneven heating of individual areas of the processed products. In this way, the possibility of temperature redistribution is ensured through the thermal conductivity of the material during its thermostating. One of the features of heat treatment is the possibility of rapid and relatively uniform heating of the product over the entire volume, which by its nature depends not so much on the thermophysical characteristics of the heated object as on the presence of moisture in it and the nature of its distribution by volume. The ability of dielectric heating is effectively used in the food industry when defrosting products. Defrosting in the microwave field allows you to speed up the process tenfold and to a large extent preserve the quality of food products. Good results are given by combined methods of defrosting microwave heating with ultrasound, as well as with the method of blowing the product with cold air. The use of microwave heating with other physical methods and energy carriers makes it possible to intensify technological processes, reduce the cost of finished products, as well as increase the nutritional and biological value of raw materials, semi-finished products and finished products.